Teachers’ Attitudes and Perspectives Towards Diglossia in Algerian Education: The Case of Moufdi Zakaria Secondary School at Maghnia - Rabahi, Hanane (LANGUAGE ART, 2025)
Diglossia is a sociolinguistic term that refers to the use of two different varieties or dialects within the same language of a community. It is found in various parts of the world. Algeria is considered a vivid example of this phenomenon, which appears through the presence of Arabic “Diglossia” that involves “The Modern Standard Arabic” and “The Algerian Arabic”. The focal point behind the current research work is to give an in-depth look at the existence of “Diglossia” as a sociolinguistics phenomenon in the Algerian Academic spaces and to shed light on the teachers’ attitudes towards including it inside classrooms by taking the teachers of “Moufdi Zakaria” Secondary school of both scientific and literary fields of study with Arabic as the language of instruction; as a case in point, and providing them by a questionnaire to get their answers and access the search results. To this end, the main findings proved that using “Diglossia” inside classrooms by the teachers can be a two-sided coin, which affects the pupils’ learning process and comprehension abilities.